Synthesis and characterization of new CoAPSO-40 and ZnAPSO-40 molecular sieves. Influence of the composition on the thermal and hydrothermal stability of AlPO4-40 -based materials - Lourenço, J. P. (2013)
Highly crystalline CoAPSO-40 and ZnAPSO-40 have been synthesized and characterized by powder XRD, TG/ DSC, SEM, EDX, 27Al, 31P and 29Si solid-state NMR, di use re¯ectance UV±VIS spectroscopy, FT IR and catalytic tests using the m-xylene isomerization and n-heptane cracking as model reactions. The simultaneous incorporation of silicon and a divalent metal in the framework of the AFR structure results in the generation of Brùnsted acid sites similar to those found in SAPO-40 and MeAPO-40. The catalytic activity of the samples for acid catalyzed reactions is higher than that of SAPO-40 with a homogeneous framework silicon distribution. The framework incorporation of cobalt or zinc results in a decrease of the thermal and hydrothermal stability of the metal bearing AFR framework, when compared with AlPO4-40 and SAPO-40.